High graphene permeability for room temperature silicon deposition: The role of defects. (March 2020) - Ronci, F.; Colonna, S.; Flammini, R.; De Crescenzi, M.; Scarselli, M.; Salvato, M.; Berbezier, I.; Jardali, F.; Lechner, C.; Pochet, P.; Vach, H.; Castrucci, P.
Abstract: Graphene (Gr) is known to be an excellent barrier preventing atoms and molecules to diffuse through it. This is due to the carbon atom arrangement in a two-dimensional (2D) honeycomb structure with a very small lattice parameter forming an electron cloud that prevents atoms and molecules crossing. Nonetheless at high annealing temperatures, intercalation of atoms through graphene occurs, opening the path for formation of vertical heterojunctions constituted of two-dimensional layers. In this paper, we report on the ability of silicon atoms to penetrate the graphene network, fully epitaxially grown on a Ni(111) surface, even at room temperature. Our scanning tunneling microscopy (STM) experiments show that the presence of defects like vacancies and dislocations in the graphene lattice favor the Si atoms intercalation, forming two-dimensional, flat and disordered islands below the Gr layer. Ab-initio molecular dynamics calculations confirm that Gr defects are necessary for Si intercalation at room temperature and show that: i) a hypothetical intercalated silicene layer cannot be stable for more than 8 ps and ii) the corresponding Si atoms completely lose their in-plane order, resulting in a random planar distribution, and form strong covalent bonds with Ni atoms. Graphical abstract: Image 109